Never again themes and sentiments about the martial law regime under President Ferdinand Marcos as expressed on Twitter - Casem, Elaine T.; Buenrostro-Cabbab, Iyra, S. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2019)
Passing narratives from one generation to another is a common and important human activity. Through this practice, the younger one become aware of the events that happened in the past, even before they were born. However, this kind of practice sometimes cause confusion and misunderstanding among people when there are contradicting claims and narratives. In recent Philippine history, one of the most controversial periods is the Martial Law period under the regime of the late President Ferdinand E. Marcos. Given this, recent events associated to the Marcoses and Martial Law such as how the Marcoses are regaining political prominence, the burial of Ferdinand Marcos at the Libangan ng mga Bayani in 2016, and the proclamation of Martial Law in Mindanao in 2017, brought out reactions and various sentiments from the public particularly in social media platforms. One of these social media site that Filipinos commonly use is Twitter.
Content analysis of the posts on Twitter that were harvested using the keywords #Never Again, #MartialLaw, #Marcos , #Philippines revealed that the prevailing themes of the narratives and sentiments about the Martial Law Regime under the late President Ferdinand Marcos were: 1)Reminiscing the State of the Philippines during the Marcos' Era, 2) Comparing the Marcos' Regime with President Rodrigo Duterte's term, 3) Commemorating the Declaration of Martial Law, and 4) Condemning Marcos' Burial at the Libingan ng mga Bayani. These themes were based on the recurring subjects of the harvested tweets, which were also supported and discussed in various literature such as monographs, journal and news articles. However, it must be noted that the resulting themes of this study only show a limited number of representations and do not absolutely stand for the overall political stance and sentiments of all the Filipino people as well as the stance of the researcher and those directly involved in the conduct of this research on the Martial Law period as a historical era and the current administration of President Duterte.
Thesis
Keywords: Martial law -- Philippines -- 1972-1981 -- Public opinion; Sentiment analysis -- Philippines; Twitter -- Political aspects -- Philippines